The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jgh3.12946
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis and overlap syndrome among Alaska Native people: Prevalence, clinical characteristics, and remission

Abstract: Background and AimHigh autoimmune hepatitis (AIH) and overlap syndrome (OS) prevalence have been previously documented among Alaska Native people. The purpose of this project is to report changes in AIH/OS prevalence over time, clinical characteristics, and factors associated with biochemical remission.MethodsWe reviewed medical records for Alaska Native/American Indian (AN/AI) patients diagnosed with AIH/OS between 1984 and 2021. Point prevalence was calculated based on AIH/OS patients alive at the end of 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Regarding AIH, the prevalence of 12.3 per 100,000 is lower than reported for most North European countries, including Denmark with a prevalence of 23.9 per 100,000 [ 12 , 24 ]. Notably, AIH is also less prevalent in Greenland than among Inuit in Alaska, who are included in the “Alaska Natives” minority population with a record-high AIH prevalence of 91.2 per 100,000 [ 11 ]. Hence, although Inuit in Greenland and Alaska share unique genetics, this seems to have little influence on the susceptibility to develop AIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding AIH, the prevalence of 12.3 per 100,000 is lower than reported for most North European countries, including Denmark with a prevalence of 23.9 per 100,000 [ 12 , 24 ]. Notably, AIH is also less prevalent in Greenland than among Inuit in Alaska, who are included in the “Alaska Natives” minority population with a record-high AIH prevalence of 91.2 per 100,000 [ 11 ]. Hence, although Inuit in Greenland and Alaska share unique genetics, this seems to have little influence on the susceptibility to develop AIH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the burden of autoimmune diseases may also resemble that of Western countries, as recently reported for autoimmune inflammatory bowel diseases [ 9 ]. Hepatologists practicing in Circumpolar areas refer to studies investigating AIH, PBC, PSC, and AIH with overlap disease in Alaska natives [ 10 , 11 ]. These studies reported a high and rising prevalence of AIH and AIH with overlap disease and a similar prevalence of PBC compared to Scandinavian countries, while no patients with PSC were identified [ 10–14 ].…”
Section: Introductionmentioning
confidence: 99%